Factor That Affect Turnover Intention in Millennial Employees - Andyani Sukmasari (Lembaga Intelektual Muda (LIM) Maluku, 2021)
The biggest challenge for companies today is thinking about various strategies in retaining millennial generation employees in order to reduce turnover intention, in which turnover intention is the reaction of employees to what is felt in the company. Factors such as strong organizational culture and employee motivation are expected to retain employees to reduce turnover intention. Therefore, the purpose of this study is to see whether organizational culture and motivation are factors that can affect turnover intention of millennial employees who are in Jabodetabek. This research is quantitative in nature, conducted by survey using a questionnaire. Data were analyzed using Structural Equation Model (SEM). The results of the first study indicate that there is an influence between organizational culture on employee motivation. Second, there is an influence between organizational culture on employee turnover intention. Third, there is an influence between motivation on employee turnover intention. Furthermore, the four motivations mediate between organizational culture and employee turnover intention in Jabodetabek